Improving Patient Satisfaction in Dental Practices through Interdisciplinary - Alhawiti , Majed Salamah; Alotaibi , Ashwag Mohammed; Shikh, Aisha Mousa Mohmad; Dahas, Mohammed Yahya; Alotaibi , Hessah Hmoud Ghazi; Alsaeed, Khalid Abdullah Saeed; Al Nawmasi, Meshal Samah; Alharby, Nawaf Abdullah; Alshammari, Eibtesam Bunder Majwal; Almotari, Khloud Shbbab; Alomran, Shaima Ahmed; Masmali, Amal Mohammed (Journal of Ecohumanism, 2024)
Background: The provision of high-quality dental care significantly impacts patient satisfaction, particularly among the elderly population, who often experience complex oral health challenges. This study explores the role of interdisciplinary collaboration between nursing staff and administrative teams in dental practices as a means to improve patient satisfaction. Methods: A systematic approach was employed to assess patient satisfaction levels of nursing and administrative personnel. The results revealed a positive correlation between effective collaboration and increased patient satisfaction, highlighting that streamlined communication and coordinated care significantly improved patient experiences. Additionally, staff reported greater confidence and efficiency in addressing patient needs when working collaboratively. Results: The findings suggest that fostering an interprofessional environment not only enhances patient outcomes but also promotes job satisfaction among healthcare providers. Conclusions: In conclusion, integrating collaborative practices in dental care settings is essential for improving patient satisfaction and overall care quality. Future efforts should focus on developing structured interprofessional education programs and collaborative frameworks that enhance teamwork between nursing and administrative staff within dental practices